(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
In the article the subject matter of a number of determinants connected to the mandatory learning of the English language since the preschool stage that is instituted in Poland has been taken up. The core curriculum of preschool education in Poland sets a frame and a basic aspect related to teaching English to children aged 3 to 6 years old. The article brings up such subjects as the goals and substance of education in the field of the English language in kindergartens as well as methods of evaluating students’ abilities and grading them. The author also brings up the question of qualifications of English teachers in preschools while paying close attention to conditions of teaching children in this age group and to the specific preparation which is expected from such tutors.